The network structure of sex partner meeting places reported by HIV-infected MSM: Opportunities for HIV targeted control. (June 2017) - Brantley, Meredith; Schumacher, Christina; Fields, Errol L.; Perin, Jamie; Safi, Amelia Greiner; Ellen, Jonathan M.; Muvva, Ravikiran; Chaulk, Patrick; Jennings, Jacky M.
Abstract: Baltimore, Maryland ranks among U.S. cities with the highest incidence of HIV infection among men who have sex with men (MSM). HIV screening at sex partner meeting places or venues frequented by MSM with new diagnoses and/or high HIV viral load may reduce transmission by identifying and linking infected individuals to care. We investigated venue-based clustering of newly diagnosed MSM to identify high HIV transmission venues. HIV surveillance data from MSM diagnosed between October 2012–June 2014 and reporting ≥1 sex partner meeting place were examined. Venue viral load was defined according to the geometric mean viral load of the cluster of cases that reported the venue and classified as high (>50, 000 copies/mL), moderate (1500–50, 000 copies/mL), and low (<1500 copies/mL). 143 MSM provided information on ≥1 sex partner meeting place, accounting for 132 unique venues. Twenty-six venues were reported by > 1 MSM; of these, a tightly connected cluster of six moderate viral load sex partner meeting places emerged, representing 66% of reports. Small, dense networks of moderate to high viral load venues may be important for targeted HIV control among MSM. Highlights: New venue-based control strategies are needed to curb HIV among MSM in the US. Local surveillance data used to identify sex partner meeting places. Evaluated MSM sex partner meeting venue affiliation networks in Baltimore, MD. A dense, centrally located set of venues was identified for targeted control. Novel application of viral load data enhanced outreach to high transmission venues.